THE PHENOMENON OF HALF-INTEGER SPIN, QUATERNIONS, AND PAULI MATRICES - FERNANDO R. GONZÁLEZ DÍAZ; RICARDO GARCÍA SALCEDO (Revista de Matemática: Teoría y Aplicaciones, 2017)
In this paper the phenomenon of half-integer spin exemplification Paul AM Dirac made with a pair of scissors, an elastic cord and chair play. Four examples in which the same phenomenon appears and the algebraic structure of quaternions is related to one of the examples are described. Mathematical proof of the phenomenon using known topological and algebraic results are explained. The basic results of algebraic structures are described quaternions H , and an intrinsic relationship with the phenomenon half-integer spin and the Pauli matrices is established.